RADIOLOGICAL MANAGEMENT OF ILEOCOLIC INTUSSUSCEPTION IN CHILDREN - Domen Plut (The Society for Children with Metabolic Disorders, 2021)
Ileocolic intussusception is an invagination of the terminal ileum into the large bowel. It is a common cause of acute abdominal pain and the most common cause of ileus in children. Most intussusceptions are idiopathic and occur within the ﬁrst three years of life. In older children, they can more often appear due to a pathological lead point. The typical clinical signs of intussusception are colicky abdominal pain, vomiting and bloody stools. If the intussusception is prolonged, perforation can occur, leading to diffuse peritonitis and septic shock. Further progression of the disease can be fatal. Therefore, quick recognition and treatment of the intussusception are crucial. Unfortunately, the clinical signs are often not typical, hence, radiology plays an important role. In diagnostics, ultrasound examination of the abdomen is the method of choice. For treatment, ultra-sound-guided hydrostatic reduction is the method of choice for non-invasive treatment. Non-invasive radiological treatment is successful in around 80% of cases. When non-invasive treatment cannot resolve the condition, urgent surgery is required. The aim of this review article is to present in detail the radiological management of ileocolic intussus-ception in children.